Bearing capacity of tapered walls: Physical modeling and numerical analysis - Kabeta, Worku Firomsa (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
This study investigates the load–displacement behavior and failure mechanisms of tapered walls using numerical methods validated against experimental data. A two-dimensional (2D) plane strain approach was adopted to effectively represent the behavior of tapered piles under vertical loading. Finite element method simulations (using both Mohr–Coulomb and hardening Mohr–Coulomb models) and limit analysis with LimitState GEO were employed to analyze three tapered wall configurations with taper angles of 0° (straight wall), 0.75° (moderately tapered), and 1.5° (sharply tapered) in dense sand. The results reveal the significant influence of taper geometry on load-bearing capacity and failure mechanisms, with the moderately tapered wall achieving the optimal balance of shaft friction and base resistance. Numerical predictions underestimated the experimental results by up to 30%, primarily due to installation effects, which were not incorporated into numerical models. This study underscores the necessity of incorporating installation-induced effects for realistic design and modeling of displacement piles.
Studia Geotechnica et Mechanica, Vol. 47, 2025, nr 3, s. 46-61
Poprzedni tytuł: Studia Geotechnica
Keywords: geotechnika - czasopisma; mechanika - czasopisma; tapered piles; centrifuge; failure mechanisms; numerical analysis; installation effects